The role of CAMP-dependent signaling systems in regulation of electrical and contractile properties of smooth muscles of the ureter in hypoxia in guinea pigs - I. V. Kovalev; J. G. Birulina; S. V. Gusakova; A. V. Nosarev; L. V. Smagliy; I. V. Petrova; V. S. Rydchenko; A. A. Leshcheva; M. A. Medvedev; G. A. Suhanova; V.. N. Vasiliyev (Бюллетень сибирской медицины)
Aim. To study the features of regulating the electrical activity and mechanical tension of smooth muscle cells (SMCs) of the guinea pig ureter as modulated by cyclic adenosine monophosphate (cAMP) in hypoxia. Materials and methods. The effects of isoprenaline (100 μM), forskolin (1 μM), 3-isobutyl-1-methylxanthine (IBMX, 100 μM) and tetraethylammonium chloride (TEA, 5 μM) on the contractile and electrical properties of isolated smooth muscle segments of the guinea pig ureter in normoxia and hypoxia were measured by the double sucrose bridge. Hypoxic conditions were created by placing the SMCs in Krebs solution containing (10.0 ± 0.2) vol. % O2. Results. It was found that an increase in the intracellular cAMP level caused by isoprenaline, the β-adrenergic receptor agonist, and activation of adenylate cyclase by forskolin, an inhibitor of phosphodiesterase IBMX, caused a decrease in the electrical and constrictor properties of the SMCs in the guinea pig ureter. The decrease in the level of oxygen in the perfusion solution resulted in the increase in the action potential amplitude and contraction of smooth muscles from the ureter. With an increase in the intracellular cAMP level, the activating effect of hypoxia on smooth muscle segments decreased. Inhibition of potassium conductivity of the ureteral SMCs with TEA in normoxia suppressed the cAMP-dependent processes induced by forskolin, whereas in hypoxia it caused the potentiation of an activating effect on the electrical activity and contractions of smooth muscle segments. Conclusion. Thus, the results suggest the involvement of cAMP-dependent signaling system in the influence of hypoxia on the electrical and contractile properties of ureteral SMCs. Modification of the intracellular cAMP level reduced the stimulatory effect of hypoxia on the smooth muscle strips of the ureter caused by increase in the ionic conductivity of the membrane and contributed to their adaptation to environmental conditions.